Pengaruh Pemberian VCO (Virgin Coconut Oil) terhadap Gambaran Histologi Tiroid Tikus Putih (Rattus norvegicus) - Haqiqoh, Habbatul; Makiyah, Sri Nabawiyati Nurul (Universitas Muhammadiyah Yogyakarta, 2008)
One of dietary alternative which can be used for overcoming thyroid dysfunction is by using Virgin Coconut Oil (VCO). The aim of this research is to know the efficacy of alternative medicine, especially VCO to improve thyroid function which can be seen from histology appearance on rat. This research is preclinical posttest only experiment with randomized control group design. The subject of this research are 25 male Spraque-Dawley strain Rattus norvegicus, 4 months and Â± 300 grams body weight. Rats were divided into 5 groups : negative and positive control, and three treatment groups. Positive control group and treatment groups will given fat first until them obese. After that, the VCO is given to three treatment groups. The dosage given was conversion of human dosage, 50 ml/day, 25 ml/day and 12,5 ml/day and will be converse in the end of week. VCO given orally everyday for 28 day, after that surgical were done to the rat, then histological thyroid object are made. The observation is seen from its follicular epithel height, follicular diameter and the colloid mass on its lumen. The data was analyzed using ANOVA test continued with Tukey test. The significant result just only shown from the diameter of follicular cells. The magnificent differences were between negative control group and treatment group which get 50 ml/day of VCO; and among positive control group with in all treatment groups. Based on this research we can conclude that VCO has significant role to improved the thyroid gland activities in white rats.Salah satu alternatif pengobatan alami untuk mengatasi masalah gangguan tiroid adalah VCO (Virgin Coconut Oil). Penelitian ini bertujuan untuk mengetahui manfaat VCO dalam membantu meningkatkan kerja kelenjar tiroid, dilihat dari gambaran histologi tiroid pada tikus putih. Metode penelitian adalah eksperimental praklinik dengan rancanganposttest randomized control group. Sampel penelitian berjumlah 25 ekor tikus putih (Rattus norvegicus) galur Spraque- Dawley jantan, umur 4 bulan dan berat badan rata-rata 300 gram. Tikus dibagi menjadi 5 kelompok yaitu kontrol positif dan negatif serta tiga kelompok perlakuan yang diberi VCO. Kelompok kontrol positifdan ketiga kelompok perlakuan digemukkan terlebih dahulu hingga mengalami obesitas. Setelah itu diberikan VCO peroral, dengan dosis hasil konversi dari dosis manusia, yaitu 50 mL/hari, 25 mL/hari, dan 12,5 mL/hari. VCO diberikan peroral setiap hari selama 28 hari kemudian tikus diterminasi dan dibuat preparat histologi tiroid. Pengamatan preparat dilakukan dengan melihat tinggi epitel sel folikel tiroid, diameter folikel, serta persentase massa koloid dalam lumen sel folikel. Untuk analisis data digunakan uji ANOVAdilanjutkan dengan uji Tukey. Hasil signifikan hanya terdapat pada gambaran diameter folikel sel kelenjar tiroid. Perbedaan tampak nyata antara kelompok kontrol negatif dengan kelompok perlakuan dosis 50 mL/hari dan kelompok kontrol positif, serta antara kelompok kontrol positif terhadap semua kelompok perlakuan yang diberi VCO. Berdasarkan penelitian ini disimpulkan bahwa minyak kelapa murni dapat membantu meningkatkan kerja kelenjar tiroid pada tikus putih.